Pelatihan Pembuatan Media Digital Untuk Tajwid Wa Tilawah Al-Qur’an Bagi Calon Guru Madrasah Diniyah Al-Muhsinat Bululwang Malang: Media Digital untuk Tajwid Wa Tilawah Al-Qur'an - M.A.Qoyyum Muliara; Fauzan, Moh; Hanik Mahliatussikah; Lala Durotus Salwa; Fatimah Mutmainnah (Tifani : Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The existence of a new era, namely the era of society 5.0, requires everyone to adapt to technology. Technology in this era is developing very quickly, so everyone can be kept from this technology. This is undoubtedly the case in the world of education. Media that was previously only print-based is now required to bring up digital media. In making digital media, skills are needed to be related to mastery of technology. Therefore this training is necessary. This training is used to help prospective teachers at Madrasah Diniyah Al-Muhsinat Bululawang Malang to create digital media in learning Tajwid wa Tilawah Al- Qur'an. Fifty participants attended the training. There are seven materials presented to encourage prospective Madrasah Diniyah Al-Muhsinat teachers to be skilled in making digital media. The methods used in this training are lectures, question and answer, micro-teaching, consultation, coaching, and mentoring. The questionnaire results from implementing this community service activity are as follows. Questionnaire results from the participants. 90% of the participants stated that the facilitators or presenters in this training were excellent, and 10% said they were good. 90% of participants stated that the presentation and mastery of the material by the presenters was excellent, and 10% said it was good. 96% of participants stated that the presented material followed the objectives, and 4% stated it was appropriate. 92% of participants stated that the presented material was exciting, and 8% stated it was interesting. 94% of participants stated that the training venue was very good, and 6% said it was good. 96% said the seminar facilities were excellent, and 4% said they were good. 90% of participants stated that the consumption was excellent, and 10% said it was good. 94% of participants stated that the training agenda was excellent, and 6% said it was good.